Spatial analysis of SARS-COV-2 variants in Peru, 2021-2022 - Montoya-Huaman, Mariangelica C. (2025)
This research aims to analyze the spatial behavior of the predominant variants of SARS-CoV-2 in Peru in the period between January 1, 2021 and June 30, 2022. A descriptive study was carried out based on the COVID-19 genomic sequencing results reported by the National Institute of Health. Exploratory analysis techniques of spatial data were applied through the free software tool Geoda. The application of global autocorrelation indices identified statistically significant spatial autocorrelation for the Gamma, Delta and ´Omicrom variants. The maps prepared from local statistics showed differences in the behavior of each variant between the provinces of Peru. The predominance of one variant over others in certain areas was concluded, as well as the presence of a different distribution pattern throughout the provinces of Peru.